Potential of ultrahigh-vacuum based surface treatments in silicon technology - Jahanshah Rad, Zahra; Miettinen, Mikko; Punkkinen, Risto; Suomalainen, Petri; Punkkinen, Marko; Laukkanen, Pekka; Kokko, Kalevi (Elsevier BV, 2026)
Ultrahigh vacuum (UHV) environment with the background pressure in the range of 1‧10−15–1‧10−11 bar is common in surface-science experiments, but UHV-based material treatments are rarely used in the current silicon technology. UHV methods might however provide a clear benefit to the technology when atomic-level cleanliness and crystalline order of Si surfaces (interfaces) as well as dry-cleaning methods for the surfaces become relevant to the development of Si devices. We have studied effects of some UHV-based treatments on the properties of Si surfaces and of thin oxide films on Si. Exposing Si, pre-cleaned by the RCA recipe with the final HF dip, to mere hydrogen (H2) gas in UHV chamber at the Si temperature of 200 °C increases a crystalline degree of the Si surface according to low-energy electron diffraction. Effects of postheating in UHV are also studied for different oxidized Si surfaces. Wet chemically oxidized (RCA without HF dip) Si was heated step-by-step up to 800 °C in UHV until the oxide removal is strongly enhanced. Both crystalline degree of the RCA chemical oxide and surface roughness increase with the UHV post-heating at 500–800 °C. Exposing native-oxide covered sidewalls of Si diodes to mere oxygen (O2) gas in UHV chamber at Si temperature of 350 °C (i) increases amount of SiO2 at the sidewalls according to x-ray photoelectron spectroscopy, (ii) decreases amount of the band-gap electron levels at the sidewalls according to scanning tunneling spectroscopy, and (iii) provides a durable decrease in the diode leakage current.